Human colon cancer cells highly express myoferlin to maintain a fit mitochondrial network and escape p53-driven apoptosis - Rademaker, Gilles (Oncogenesis, 2019)
Colon adenocarcinoma is the third most commonly diagnosed cancer and the second deadliest one. Metabolic reprogramming, described as an emerging hallmark of malignant cells, includes the predominant use of glycolysis to produce energy. Recent studies demonstrated that mitochondrial electron transport chain inhibitor reduced colon cancer tumour growth. Accumulating evidence show that myoferlin, a member of the ferlin family, is highly expressed in several cancer types, where it acts as a tumour promoter and participates in the metabolic rewiring towards oxidative metabolism. In this study, we showed that myoferlin expression in colon cancer lesions is associated with low patient survival and is higher than in non-tumoural adjacent tissue. Human colon cancer cells silenced for myoferlin exhibit a reduced oxidative phosphorylation activity associated with mitochondrial fission leading, ROS accumulation, decreased cell growth, and increased apoptosis. We observed the triggering of a DNA damage response culminating to a cell cycle arrest in wild-type p53 cells. The use of a p53 null cell line or a compound able to restore p53 activity (Prima-1) reverted the effects induced by myoferlin silencing, confirming the involvement of p53. The recent identification of a compound interacting with a myoferlin C2 domain and bearing anticancer potency identifies, together with our demonstration, this protein as a suitable new therapeutic target in colon cancer.